Gender Differences in Executive Functions of Patients Operated for Mild to Moderate Epidural Hematoma - Shweta Singh; Seema Rani Sarraf; Adarsh Tripathi; Bal Krishna Ojha; Amandeep Singh (Indian Journal of Neurosurgery, 2024)
Background Impairment in neurocognitive functions are commonly followed by Epidural hematoma (EDH) . This cross-sectional study was aimed to study gender differences in neurocognitive functions in mild to moderate epidural hematoma patients (43 male and 19 female patients) post-surgery using standardized assessment tools of comprehensive neurocognitive function attention, speed, working memory, fluency, set-shifting, perseveration, planning and response inhibition.